Rural Livelihoods and Vulnerability Towards Natural Disasters: An Empirical Exploration from Selected Villages of District Gilgit, Pakistan: Rural Livelihoods and Vulnerability Towards Natural Disasters: An Empirical Exploration from Selected Villages of District Gilgit, Pakistan - Ahmed, Israr; Karim, Rehmat; Muhammad, Faqeer; Akhter, Javed; Abdul Latip, Normah; Ullah, Kifayat; Nilofar, Memoona (International Journal of Economic and Environmental Geology, 2020)
Present study explores livelihoods of rural households and their vulnerability towards natural hazards in three selected villages of district Gilgit, a far-flung mountainous area in north of Pakistan. Data were collected from 180 households by using purposive and snowball sampling techniques. Moreover, Livelihood Vulnerability Index (LVI) and descriptive statistics were used for data analysis. The standard value of LVI ranges from 0 to 1, whereby the higher value of LVI shows higher vulnerability. LVI for each village was calculated using the data of seven components i.e. socio demography, livelihood strategies, social networks, food, health and education, water, natural disasters and climate vulnerability. The results suggest that the rural households of district Gilgit are vulnerable to natural disasters and Gilgit is most vulnerable in food and social network and least vulnerable in terms of demographic profile. Lastly, the overall value of LVI for district Gilgit is 0.34